2022
DOI: 10.1038/s41598-022-16112-7
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study using an individualized nomogram to predict the success rate of external cephalic version

Abstract: To establish a clinical-based nomogram for predicting the success rate of external cephalic version (ECV) through a prospective study. This was a single-center prospective study that collected eligible breech pregnant women. 152 participants were enrolled in the training cohort, who received ECV procedures performed by a single operator. We used the training cohort to establish regression equations and prediction models. These variables include maternal factors (age, operation gestational age, pre-pregnancy BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…While the large majority of articles studied maternal weight or BMI, only a few indicated whether this was collected or intended to be a pregravid, peri-ECV, or peripartum BMI. Of the 8 models using some form of maternal weight or BMI, one model used BMI at ECV 46 , one model used the BMI increase from prepregnancy to ECV 39 , two models from the same article used pre-pregnancy BMI 36 , and 4 models were not clear on when BMI was evaluated 30,31,41,44 .…”
Section: Predictor Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…While the large majority of articles studied maternal weight or BMI, only a few indicated whether this was collected or intended to be a pregravid, peri-ECV, or peripartum BMI. Of the 8 models using some form of maternal weight or BMI, one model used BMI at ECV 46 , one model used the BMI increase from prepregnancy to ECV 39 , two models from the same article used pre-pregnancy BMI 36 , and 4 models were not clear on when BMI was evaluated 30,31,41,44 .…”
Section: Predictor Variablesmentioning
confidence: 99%
“…The remaining 13 new articles used datasets, proposed models, and were performed by researchers that were entirely distinct from the 8 original articles. Of these articles, two were from the same team of authors and used the same dataset; Anand 2019 used the dataset to create a model predicting cephalic position after the ECV, while the Palepu 2021 created a model to predict vaginal delivery 30,31 The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 32,33 , while the remaining 9 proposed a single model each [34][35][36][37][38][39][40][41][42] (Figure 2). Two of the articles had an erratum: one was trivial 36,43 and only modi ed a sentence in the abstract, while the other was a correction of a gure describing the decision tree model 37,44 .…”
Section: Relationships Between Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these articles, two were from the same team of authors and used the same dataset; Anand et al used the dataset to create a model predicting cephalic position after the ECV, while the Palepu et al created a model to predict vaginal delivery 34,35 . The remaining 11 articles were completely independent from each other; two of these articles proposed two models each 36,37 , while the remaining 9 proposed a single model each [38][39][40][41][42][43][44][45][46] (Figure 2). Two of the articles had an erratum: one was trivial 40,47 and only modified a sentence in the abstract, while the other was a correction of a figure describing the decision tree model 41,48 .…”
Section: Relationships Between Articlesmentioning
confidence: 99%
“…The results of the study quality assessment based on the signaling questions are shown in Table 4. Out of 17 new articles, 10 studies were identified as having low overall risk of bias and high study quality 22,[33][34][35][36]39,41,[44][45][46] , 6 studies were identified as having moderate bias and moderate study quality 29,37,38,42,43,47 , and 1 was considered to have high bias and low quality 30 . This is in addition to Velzel et al's assessment of the 8 prior articles of which 4 were low risk of bias and high study quality and 4 were moderate risk of bias and study quality 10 .…”
Section: Quality and Biasmentioning
confidence: 99%